Theorizing Scriptures : New Critical Orientations to a Cultural Phenomenon - Wimbush, Vincent L. (Book collections on Project MUSE., 2008)
Historically, religious scriptures are defined as holy texts that are considered to be beyond the abilities of the layperson to interpret. Their content is most frequently analyzed by clerics who do not question the underlying political or social implications of the text, but use the writing to convey messages to their congregations about how to live a holy existence. In Western society, moreover, what counts as scripture is generally confined to the Judeo-Christian Bible, leaving the voices of minorities, as well as the holy texts of faiths from Africa and Asia, for example, unheard. In this innovative collection of essays that aims to turn the traditional bible-study definition of scriptures on its head, Vincent L. Wimbush leads an in-depth look at the social, cultural, and racial meanings invested in these texts. Contributors hail from a wide array of academic fields and geographic locations and include such noted academics as Susan Harding, Elisabeth Shüssler Fiorenza, and William L. Andrews. Purposefully transgressing disciplinary boundaries, this ambitious book opens the door to different interpretations and critical orientations, and in doing so, allows an ultimately humanist definition of scriptures to emerge.